Todos somos artistas: um diálogo entre Nietzsche e Beuys - Nunes, Juliana Bernabé (2010)
The intention of this thesis is to think the guiding principle that grounds and makes both the artistic conception of Friedrich Nietzsche and Joseph Beuys, in order to understand the element that brings them together in the same perspective in relation to art, namely that it is the proper task of life. Expanding the horizon of the issues of art beyond the aesthetic discussions, both view it as a pathos, an impulse, ie, as a disposition of man to himself, to the life he himself is. It is here, therefore, the establishment of a dialogue between the philosopher and the artist about art as the constitution of life itself, of man's existence on this earth, and so long as the soil where it can make a decisive criticism to the decadence of the modern position.